Brill's companion to Hellenistic epigram : down to Philip - Bing, Peter; Bruss, Jon Steffen (Brill's companions in classical studies., 2007)
Important research in recent decades, along with the publication of P.Mil.Vogl. VIII 309 ('the Milan Posidippus papyrus') in 2001, have reinvigorated the study of Hellenistic epigram. Yet, scholarship on this genre often remains fragmented according to disciplinary sub-specialty and approach: some scholars focus on poets of Meleager's Garland, others on Philip's; some on inscriptional epigram, others on literary; each approaching the genre with different motives and questions. In this volume, expert scholars offer those less familiar with the genre an introduction to all aspects of Hellenistic epigram--from models and forms inherited from inscriptional epigram to poetology, sub-genera, epigrammatic intertexts, and ancient and modern reception. Even specialists will find here fresh explorations of epigram, along with new directions for scholarship.